Research Trends of SDGs Integrated Science Interactive Learning Media to Improve Students' Science Literacy: Bibliometric Analysis - Ferniawan Ferniawan; Agus Ramdani; Joni Rokhmat; A Wahab Jufri; AA Sukarso (Jurnal Penelitian Pendidikan IPA, 2025)
This study examines the trend of interactive science learning media integrated with SDGs to improve students' science literacy. Improving science literacy is considered important considering the complexity of global challenges that require scientific understanding in sustainable decision-making. This study aims to provide a bibliometric review of publications related to interactive science learning media integrated with SDGs to improve students' science literacy during the period 2015-2024. Data were collected from Google Scholar using analysis tools such as Publish or Perish and Dimension.ai, resulting in 1,000 documents identified and selected using the PRISMA guidelines. The analysis was carried out using bibliometric and content analysis methods, supported by VOSviewer software to visualize keyword trends and emerging research patterns. The results show a significant increase in the trend of publications of interactive science media integrated with SDGs, with a peak in 2023. The dominance of keywords such as "citizen science," "sustainability," and "media literacy" indicates the important role of science literacy in preparing students to face global issues through critical thinking skills, collaboration, and digital literacy. The results of this study indicate that interactive learning media based on SDGs has become the main focus in the development of science education that is relevant and contextual to the needs of the 21st century. Although there are challenges in its implementation, the integration of SDGs in science education makes a significant contribution in creating a generation that is more aware of sustainability and is globally responsible.